Making Good?: A Study of How Senior Penal Policy Makers Narrate Policy Reversal - Annison, Harry (The British journal of criminology, 2024)
This paper provides insights into the predominant styles of political reasoning in England and Wales that inform penal policy reform. It does so in relation to a particular development that constitutes a dramatic, perhaps even unique, wholesale reversal of a previously introduced market-based criminal justice delivery model. This is the ‘unification’ of probation services in England and Wales, which unwound the consequential privatization reforms introduced less than a decade earlier. This paper draws on in-depth interviews with senior policy makers to present a narrative reconstruction of the unification of probation services in England and Wales. Analogies with desistance literature are drawn upon in order to encapsulate the tensions posed for policy makers as they sought to enact this penal policy reform.